Review of the PE Metrics cognitive assessment tool for fifth grade students - Hodges Michael; Lee Chong; Lorenz Kent A.; Cipriani Daniel (Sciendo, 2015)
Study aim: this study examined the item difficulty and item discrimination scores for the HRFK PE Metrics cognitive assessment tool for 5th-grade students.